1996
DOI: 10.1007/s002340050257
|View full text |Cite
|
Sign up to set email alerts
|

Compressive myelopathy in fluorosis: MRI

Abstract: We examined four patients with fluorosis, presenting with compressive myelopathy, by MRI, using spin-echo and fast low-angle shot sequences. Cord compression due to ossification of the posterior longitudinal ligament (PLL) and ligamentum flavum (LF) was demonstrated in one and ossification of only the LF in one. Marrow signal was observed in the PLL and LF in all the patients on all pulse sequences. In patients with compressive myelopathy secondary to ossification of PLL and/or LF, fluorosis should be consider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
9
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 0 publications
2
9
1
Order By: Relevance
“…The disease more rarely affects the cervical spine. 33,34 Only 3 cases of multiple level involvement 15,20 similar to that in patient Nos. 6 and 11 have been reported in the literature.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…The disease more rarely affects the cervical spine. 33,34 Only 3 cases of multiple level involvement 15,20 similar to that in patient Nos. 6 and 11 have been reported in the literature.…”
Section: Discussionsupporting
confidence: 65%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13] A few cases have been reported in the Middle East 14 and in India (5 cases). 15,16 Only one observation has been reported in an African American, 17 and the present authors reported the first case in an African Caribbean patient. 18 Published series are rare, 19 -26 all concerning Japanese subjects.…”
mentioning
confidence: 74%
“…A significant decrease in the vitamin C levels was observed in the individuals living in the fluoride affected area (Group 1) when compared to the individuals living in the fluoride unaffected area (Group 2) in the study. Teotia M et al 12 and Gupta et al 13 also reported similar findings of our study, but no reports are available regarding the effect of vitamin C supplementation therapy. Our study also states the inverse relation between oxidative stress and antioxidant levels with respect to the toxic effects of fluoride could be due altered antioxidants.…”
supporting
confidence: 80%
“…8 Although neurological complications may occur in 10% of cases with skeletal fluorosis, mostly in the later stages of disease, 1 myelopathy due to ossification of the posterior longitudinal ligament and/or ligamentum flavum in patients with skeletal fluorosis has been uncommonly reported and mostly localized in the lower thoracic part of the spinal cord. 8,9 To the best of our knowledge, the association of high cervical myelopathy and skeletal fluorosis has not been reported.…”
Section: Discussionmentioning
confidence: 74%